Community-Based Health Intervention Strategy through Local Product Diversification for Diabetes Mellitus - Said, Asbath; Ari Nofitasari; Ayu Ningtyas Putri (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Diabetes mellitus (DM) remains a major global health challenge, with prevalence increasing both worldwide and in Indonesia, including Kendari City, Southeast Sulawesi. Preventive strategies that integrate community engagement and local food systems are urgently needed. Methods: This study employed a qualitative descriptive design to explore community experiences, perceptions, and involvement in diversifying scad fish into value-added products as a strategy for DM prevention. Research was conducted in Kendari with 32 participants, including health cadres, women’s groups, small and medium enterprise (SME) fish processors, and community leaders. Data collection methods consisted of in-depth interviews, focus group discussions, participant observation, and document review. Thematic analysis was applied using Miles and Huberman’s framework, supported by triangulation and member checking to ensure credibility. Results: Findings revealed that scad fish, though abundant and affordable, was underutilized due to low preference compared to other fish species. Through participatory processes, communities co-developed scad fish floss and crackers, which were widely accepted for their practicality, longer shelf life, and cultural compatibility. Mothers reported replacing sugary snacks with scad-based products, indicating positive dietary shifts, while SMEs and women’s groups gained new livelihood opportunities. Community involvement particularly by health cadres and local leaders was identified as the central factor ensuring acceptance, sustainability, and dissemination of the intervention. Conclusions: The diversification of scad fish into floss and crackers demonstrates a culturally relevant, sustainable, and community-driven approach to DM prevention. Beyond improving nutrition, this intervention also strengthens local economies and promotes social empowerment. The study provides a model for integrating health promotion with local food resources, offering implications for future community-based strategies in resource-rich settings.